Guinea : Technical Assistance Report-Report on Technical Assistance Mission on External Sector Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
A technical assistance (TA) mission visited Guinea during July 9-20, 2018, as part of the project funded by the Government of Japan to improve external sector statistics (ESS) in 17 Francophone African countries. This was the third mission under this project following the missions in 2016 and 2017. The mission was hosted by the Central Bank of the Republic of Guinea (BCRG), which is responsible for compiling ESS. The mission addressed the following main issues (i) improvement of the surveys on migrant remittances and informal trade; (ii) perform detailed technical work to improve ESS; and (iii) participation in the coordinated direct investment survey (CDIS) and the quarterly external debt statistics (QEDS) database. The mission also reviewed the status of implementation of the recommendations from the previous TA missions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet